Influence of yearlong training on the state of cardiovascular, autonomic nervous system and physical performance in female 400 meters runners - Ye. L. Mikhalyuk; M. V. Didenko; S. N. Malakhova (Patologìâ)
Aim of the research – identification and comparison of heart rate variability, central hemodynamics and physical performance in 400 meters runners from the III category to masters of sports of international class (MSIC) in the annual cycle of the training process.